6(2a+10)=5(a+4)+5

Simple and best practice solution for 6(2a+10)=5(a+4)+5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(2a+10)=5(a+4)+5 equation:



6(2a+10)=5(a+4)+5
We move all terms to the left:
6(2a+10)-(5(a+4)+5)=0
We multiply parentheses
12a-(5(a+4)+5)+60=0
We calculate terms in parentheses: -(5(a+4)+5), so:
5(a+4)+5
We multiply parentheses
5a+20+5
We add all the numbers together, and all the variables
5a+25
Back to the equation:
-(5a+25)
We get rid of parentheses
12a-5a-25+60=0
We add all the numbers together, and all the variables
7a+35=0
We move all terms containing a to the left, all other terms to the right
7a=-35
a=-35/7
a=-5

See similar equations:

| t2=1 | | 49m2+5m=0 | | 61-4k=2k+13 | | 19+-7p=-2 | | 9x-7+2x=7x-9+4x | | -4p+10=4-2p | | 1=k−1 | | 1.0825x=45 | | -x+7=2x-6-4x | | 3x+4/5=7x-2x | | m/2+-8=-5 | | -100=15t-4.9t^2 | | 42-7k=4k+9 | | |5x-4|=|2x-1| | | 6x+16=8x+30 | | 6y=12B | | |5x-4|=|-2x-1| | | 9(x-5)=-15x+3 | | |-5x-4|=|-2x-1| | | 13x+6=-1x-8 | | t/2+15=18 | | x-100=6x+20 | | -3=d/4+-7 | | 6x^2+4x=10-7x | | n/4+5.6=3.85 | | 104=4-4(-1+3x) | | 155=5x+4(4x+2) | | 25-4x=-(x-26) | | 5=z/3+3 | | 1/3(6x+9)=5(2x-3) | | 5x+14=12+8x+2 | | -19c+20=-20c |

Equations solver categories